High refractive index La-rich lanthanum borate glasses composed of isolated BO3 units. Issue 29 (18th June 2019) - Masuno, Atsunobu; Iwata, Takashi; Yanaba, Yutaka; Sasaki, Shunta; Inoue, Hiroyuki; Watanabe, Yasuhiro
Abstract : The simple environment around the B atom in high refractive index La-rich La2 O3 –B2 O3 glasses caused wide transmittance in the IR region. Abstract : La2 O3 –B2 O3 binary glasses were prepared by containerless processing using a levitation technique. The bulk glass-forming region in a B-rich composition was extended compared to that using conventional melt-quench techniques. Furthermore, additional glass formation was realized in an La-rich composition. The glass transition temperature and crystallization temperature of La-rich glasses are much higher than those of B-rich glasses. Both B- and La-rich glasses were colorless and transparent and had a high refractive index with low wavelength dispersion in the visible region. With the increase of the La2 O3 content, the optical absorption edge in the ultraviolet (UV) region shifts to a long wavelength. An additional infrared (IR) transmittance window was observed in La-rich glasses, indicating that the La-rich borate glasses are expected to be used in optical components in a wide wavelength region. Local structural analyses using 11 B magic-angle spinning (MAS) nuclear magnetic resonance (NMR) and Raman scattering spectra revealed that every B-atom in La-rich glasses formed a planar trigonal BO3 unit and these BO3 units were entirely isolated. The evident difference from B-rich glasses where B-atoms formed a complex network structure with BO3 and BO4 units caused the characteristic physical and optical properties of La-rich glasses.